(untitled) (CIPEEX, 2025)
Introduction: Prenatal screening is crucial for ensuring the health and well-being of both the pregnant woman and the baby, from preconception through pregnancy. It consists of a variety of tests aimed at the early detection of congenital diseases that can be transmitted vertically, allowing for interventions in family planning and treatment options. Objective: To analyze the impact of prenatal screening on the incidence of preventable diseases during pregnancy. Methodology: This is an integrative literature review using descriptors such as "pregnancy," "prenatal diagnosis," "prenatal care," and "screening" in the PubMed database, Virtual Health Library (BVS), and Scientific Electronic Library Online (SciELO). Twelve articles were reviewed, and five were selected as relevant to the guiding question, all published in the last five years. Results: Prenatal screening aims to ensure the well-being of the pregnant woman and the baby by enabling the early identification of diseases during pregnancy. According to the reviewed articles, the impacts of prenatal care include increased detection of preventable diseases and, consequently, improved planning for the prevention and treatment of these congenital conditions. Bueno Aguiar’s article highlights that neonatal diagnosis offers the opportunity for early intervention before the consequences of cystic fibrosis become irreversible. Trindade’s research indicates a rise in HIV detection rates among pregnant women in recent years, underscoring the need for improved quality in healthcare services. Conclusion: The significant importance of screening programs for pregnant women is evident, particularly regarding the role of Primary Health Care in providing quality gestational monitoring and treatment upon diagnosis, using simple and cost-effective technologies for the population.